The health paradoxes of social media influencers - Martin Mileros; Charlotte Norrman; Christina Öberg (Journal of Innovation and Entrepreneurship)
Abstract This paper describes and discusses social media influencers’ health-related costs of keeping traction as influencers. The paper is based on interviews and social media posts. Four paradoxes highlight the social media influencers’ contradictory circumstances: (1) the social media influencer’s well-being is situated between not being dependent on income and earning the income to avoid monetary stress; (2) well-being becomes associated with playing a role, while authenticity is crucial for the influencer; (3) the premises of being a successful social media influencer is what creates their despair; and (4) being exposed as a healthy role model risks harming the well-being of the social media influencer. The paper takes a unique perspective on social media influencers, focusing on their well-being rather than their promotional power. The paper helps to create socially sustainable conditions for influencers, while it adds to theory through outlining influencers’ paradoxical conditions.